Solution chemistry : minerals and reagents - Somasundaran, P., 1939- (Developments in mineral processing, 2006)
Surfactants have been used for many industrial processes such as flotation, enhanced oil recovery, soil remediation and cleansing. Flotation technology itself has been used in industry since the end of the 19th century, and even today it is an important method for mineral processing and its application range is expanding to other areas. This technology has been used in the treatment of wastewater, industrial waste materials, separation and recycling of municipal waste, and some unit processes of chemical engineering. The efficiency of all these operations depends primarily on the interactions among surfactants, solids and media. In this book, the fundamentals of solution chemistry of mineral/surfactant systems are discussed, as well as the important calculations involved. The influence of relevant physico-chemical conditions are also presented in detail. * Introduces the fundamentals of solution chemistry of mineral/surfactant systems and important calculations involved * Discusses the influence of relevant physico-chemical conditions * Presents the relationship between the molecular structure of the flotation regents of solution chemistry and its characteristics.